Spreading gravity currents with temperature-dependent viscosity - Sansom, Ahmos (2000)
The spreading of a fluid under gravity has many important industrial and geophysical applications and has been the focus of much research. Variations in the thermal properties of the fluid have often been neglected. This thesis introduces a series of models incorporating fluids having temperature-dependent viscosity and vertical cross-sectional profile of small aspect ratio to show the important effects that cooling can have on the flow field. The numerical results show features that are commonly observed in experiment and lava dome growth, such as plateauing and fingering.